2022
DOI: 10.1097/md.0000000000032368
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib efficacy and safety in patients with advanced NSCLC harboring MET alterations: A real-life data of Turkish Oncology Group

Abstract: Crizotinib is a multikinase inhibitor, effective in non-small cell lung cancer (NSCLC) harboring mesenchymal-epidermal transition (MET) alterations. Although small prospective studies showed efficacy and safety of crizotinib in NSCLC with MET alterations, there is limited real-life data. Aim of this study is to investigate real-life efficacy and safety of crizotinib in patients with advanced NSCLC harboring MET alterations. This was a retrospective, multicenter (17 centers) study of Turkish Oncology Group. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Preoperative targeted-therapy induction had promising hopes for better overall survival. The US Food and Drug Administration approved Crizotinib as the first drug to treat NSCLC harboring ALK or ROS-1 fusions [28]. Chen [26] reported that five clinical trials for stage III using targeted therapy agents such as erlotinib and gefitinib managed on one hand to shrink the tumor; nonetheless, on the other hand, the improvement in overall survival relative to neoadjuvant chemotherapy was indefinite [26].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative targeted-therapy induction had promising hopes for better overall survival. The US Food and Drug Administration approved Crizotinib as the first drug to treat NSCLC harboring ALK or ROS-1 fusions [28]. Chen [26] reported that five clinical trials for stage III using targeted therapy agents such as erlotinib and gefitinib managed on one hand to shrink the tumor; nonetheless, on the other hand, the improvement in overall survival relative to neoadjuvant chemotherapy was indefinite [26].…”
Section: Introductionmentioning
confidence: 99%